Translation and Spread of Hispanic Litterature in Fascist Italy (Anclajes, 2021)
The main purpose of this paper is to demonstrate the existence of an Italian interest in Latin American culture under fascist dictatorship. Having given rise to an increasing dissemination of Hispanic culture in Italy, cultural relations between Italy, Spain, and Latin America in the 20s and 30s will be examined. During that period, there was a very strong ideological affinity between Italy and Spain, which explains why the Italian government promoted Spanish-language literature more than others did. Even so, studies show that the spread of Hispanic editorial production in Italy was probably due to accidental meetings between publishers and not to a clear governmental policy. As for Hispano-American literature, the name Mario Puccini stands out as one who helped make modernist writers (such as Rufino Blanco Fombona and Amado Nervo) known in Italy. Accordingly, the essay’s main objective is to focus on his professional activity in order to better understand which was the starting point for members of Cristoforo Colombo Institute (1923-1935), the only Italian government body responsible for the promotion of Hispanic culture.
Keywords: fascism; cultural policy; Hispanic literature; Mario Puccini; Cristoforo Colombo Institute